2016
DOI: 10.1007/s12160-016-9850-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Social- and Neurocognitive Model of Physical Activity Behavior in Older Adults with Metabolic Disease

Abstract: Background Despite the proven benefits of physical activity to treat and prevent metabolic diseases, such as diabetes (T2D) and metabolic syndrome (MetS), most individuals with metabolic disease do not meet physical activity (PA) recommendations. PA is a complex behavior requiring substantial motivational and cognitive resources. The purpose of this study was to examine social cognitive and neuropsychological determinants of PA behavior in older adults with T2D and MetS. The hypothesized model theorized that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 49 publications
1
22
0
1
Order By: Relevance
“…Notwithstanding, a first assumption would be that older adults who have better memory abilities and/or better attentional control engage themselves more easily in active behaviors. This explanation is reinforced by previous research that has reported that the use of memory strategies facilitates the management of daily living activities [ 7 ], medication adherence [ 19 , 26 ], and PA [ 15 ]. To our knowledge, only the study carried out by Olson et al [ 26 ] reporteda relationship between attention and adherence to PA and postulated that controlled inhibition is critical to successful behavior changes.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Notwithstanding, a first assumption would be that older adults who have better memory abilities and/or better attentional control engage themselves more easily in active behaviors. This explanation is reinforced by previous research that has reported that the use of memory strategies facilitates the management of daily living activities [ 7 ], medication adherence [ 19 , 26 ], and PA [ 15 ]. To our knowledge, only the study carried out by Olson et al [ 26 ] reporteda relationship between attention and adherence to PA and postulated that controlled inhibition is critical to successful behavior changes.…”
Section: Discussionmentioning
confidence: 72%
“…As highlighted by McDonald-Miszczak et al [ 25 ], despite a lack of clear identification of the cognitive functions implied in the adherence process, the research literature has identified several cognitive processes that can be considered to be responsible for psychological disturbances and nonadherence when they are impaired. Recently, Olson et al [ 26 ] reported that cognitive functions such as working memory, controlled inhibition, attention, and task switching predicted PA adherence 6 months after the end of a PA program in older adults with metabolic diseases. Other studies have identified prospective memory [ 14 , 27 ], metamemory [ 8 , 28 ], and attentional control [ 22 , 29 , 30 ] as determinants of high levels of cognitive functioning.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to examine the association of these potentially modifiable psychological influences on PA within this older adult subgroup. In previous studies of older adults, the relative importance of self-efficacy and self-regulation for Short title: PSYCHOLOGICAL AND ENVIRONMENTAL CORRELATES OF PHYSICAL ACTIVITY 14 predicting PA were not conclusive (Mudrak et al, 2017;Olson et al, 2017;Reyes Fernández et al, 2014). Inconsistencies regarding the relative importance of selfefficacy versus self-regulation might be partially explained by differences in the cognitive functioning of participants in different studies.…”
Section: Discussionmentioning
confidence: 92%
“…Some previous studies have reported self-efficacy and self-regulation correlates with PA, even among older adults (Mudrak, Slepicka, & Elavsky, 2017;Reyes Fernández, Montenegro Montenegro, Knoll, & Schwarzer, 2014;Olson et al, 2017). Additionally, an ecological model of active living (Sallis et al, 2006) has been applied within past PA research (Rhodes, & Nasuti, 2011), highlighting the long term effects that environmental factors can have on large populations.…”
Section: Introductionmentioning
confidence: 99%
“…Algunos estudios han constatado que el incremento de la autoeficacia contribuye a favorecer el bienestar y la calidad de vida, pero no solo eso, sino que promueve la capacidad de autodeterminación de las personas mayores (Mudrak, Stochl, Slepicka, & Elavsky, 2016;Suchy, Williams, Kraybill, Franchow & Butner, 2010). La mayoría de estudios en relación a esta dimensión se han fundamentado en el potencial de la autoeficacia para la mejora del rendimiento físico y cognitivo, las habilidades de la vida diaria y la salud física y mental (Olson et al, 2017;O´Shea et al, 2016;Resnick, Luisi, & Vogel, 2008;Thornton et al, 2016).…”
Section: Los Componentes Psicosociales Y Emocionales Como Focos Emergunclassified